Construction of 3D aerogels consisting of cellulose and BNNSs bridged by AgNPs for enhancing thermal and tribological properties of polyurethane composites - Yu He; Yuanya Zhang; Yongjun Zhou; Junya Yuan; Xuehu Men (Nano Materials Science)
Waterborne polyurethane (WPU) is attracting widespread attention in the friction field, but pure WPU cannot meet the wear resistance requirements due to poor thermal and self-lubricating properties. Herein, a novel cellulose/BNNSs-AgNPs aerogel (CBAg) composed of zero-dimensional silver nanoparticles (AgNPs), one-dimensional cellulose and two-dimensional boron nitride nanosheets (BNNSs) was successfully fabricated. Specifically, AgNPs were loaded onto the surface of BNNSs, which could serve as bridges to connect adjacent BNNSs. Cellulose was used to construct a 3D skeleton structure for stabilizing better dispersion of inorganic fillers. Finally, the thermal and tribological properties of CBAg-WPU were improved compared to pure WPU, with a 69% increase in thermal conductivity and an 89% reduction in wear rate. This was attributed to the load-bearing capacity of cellulose and outstanding thermal and lubricant capability of BNNSs-AgNPs. In addition, BNNSs and AgNPs inside the aerogel were transferred to the sliding interface and participated in the formation of high-quality friction transfer film, further endowing CBAg-WPU composites prominent tribological performance. Therefore, the novel design of 3D hybrid aerogels provided a promising avenue to improve the tribological performance of WPU composites.